Household waste management behavior: A study of community practices in Barrang Lompo Island, South Sulawesi - Ridwan, Muhammad; Amansyah, Munawir; Syarfaini, Syarfaini (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Previous studies on household waste management have predominantly focused on urban settings with established infrastructure, leaving a gap in the understanding of waste-related behaviors in remote island communities. This study explores the behavior of residents toward household waste management on Barrang Lompo Island, Kecamatan Sangkarrang, South Sulawesi. Employing a quantitative descriptive observational design, this research surveyed 307 respondents from a total of 1,324 households using non-probability convenience sampling. The independent variables included knowledge, attitude, and practice, while the dependent variable was household waste management. The results revealed that community knowledge was predominantly good (76.6%), although attitudes were mainly less favorable (60.2%), and actions were generally poor (51.5%). These findings suggest that while awareness is relatively high, it has not translated into consistent behavior, indicating a disconnect between knowledge and practice. The study underscores the urgent need for targeted environmental education, local regulation, and collaboration with public agencies to enhance sustainable waste practices. These implications are especially vital for remote and densely populated island communities where poor waste handling poses severe environmental and public health risks.